Gender inequities in household labor predict lower sexual desire in women partnered with men - Harris, Emily A; Gormezano, Aki M.; van Anders, Sari M. (Archives of Sexual Behavior, 2022)
Low sexual desire in women is usually studied as a problem, one that is located within women. However, other possibilities exist, including known gender inequities related to heteronormative gender roles. In this study, we provide the first test of the theory that heteronormativity is related to low sexual desire in women partnered with men, focusing specifically on inequities in the division of household labor. In two studies with women who were partnered with men and had children (Study 1, N = 677; Study 2, N = 396), performing a large proportion of household labor was associated with significantly lower sexual desire for a partner. Together, the results suggest that this association was mediated by both perceiving the partner as a dependent and perceiving the division of labor as unfair. These results support the heteronormativity theory of low sexual desire in women partnered with men, and show that gender inequities are important, though understudied, contributors to low desire in women partnered with men. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; désir; hétéronormativité; hétérosexisme; projet charge mentale; périodes historiques; santé; sexualité; systèmes d'oppressions; thématiques; travail; travail domestique

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer